The Relationship Between Students' Understanding of PIR-R Organization With its Activity at Sma N 1 Koto XI Tarusan - Wahyuni, Dinda; Sunarti, Vevi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by student activity in the PIK-R organization at SMA N 1 Koto This research aims to see a picture of students' understanding of the PIK-R organization, see a picture of students' activity in the PIK-R organization, and see the relationship between students' understanding of the PIK-R organization and their activity at SMA N 1 Koto XI Tarusan. This research uses a quantitative, correlational type approach. The population of this research is all students who are members of PIK-R at SMA N 1 Koto XI Tarusan, totaling 24 respondents. Meanwhile, samples were taken using a total sampling technique, namely 100% (24) and trials were carried out at other schools that had the same characteristics. Data collection techniques using tests and questionnaires distributed directly to respondents. Meanwhile, the data analysis technique uses percentage formulas and rank order formulas. The research results show that students' understanding of the PIK-R organization is still relatively low. Students in organizations have low activity, and there is a significant relationship between students' understanding of the PIK-R organization and their activity. This means that the higher the student's understanding of the PIK-R organization, the more active the student is in the organization, but conversely, the lower the student's understanding of the PIK-R organization, the lower the student's activeness.                                                                                           Keywords : Understanding, PIK-R organization, activeness